Limnological features of Pandoh reservoir, Himachal Pradesh - Kaushal, D K; Joshi, H C; Kumar, S (Indian Journal of Fisheries, 2011)
Pandoh reservoir, a 200 ha impoundment situated across the river Beas in the district Mandi, Himachal Pradesh was surveyed for its limnological features. The low values of total alkalinity (24-44 ppm), specific conductivity (86.4â€”97.2 |j,mhos/cm), low temperature regime (10.5-16.5Â°c) and nutrient status point towards temperate condition and oligotrophic tendencies of the reservoir . This is strengthened by the poor plankton count. Suggestions pertaining to management and development of the fisheries in the reservoir were made.